Computational Thinking berbasis Unplugged Activity Menggunakan Tugas Algoritma pada Anak Usia Dini - Kamil, Nurhusna; Fitri, Zayyana Zahrotul; Melynda, Diajeng Ristinia (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
Computational thinking skills based on unplugged activity by collecting algorithmic tasks have recently become a concern. Various activities can be a way to stimulate these abilities. Fun cooking is one alternative that can be used for preschool children. This study aims to describe how fun cooking activities can stimulate computational thinking skills that have been widely applied by early childhood education institutions. The research sample of 18 children was aimed at students of Angkasa Lanud Adisucipto Kindergarten, Yogyakarta. Data collection techniques used interviews, documentation and direct observation. The results of the study showed that there were several algorithmic tasks that were understood by the research sample when carrying out fun cooking activities; 1) students orderly listened to the teacher's explanation regarding the activity process to be carried out, 2) students knew the flow of activities to be carried out, 3) some cooking activities required repeated processes. The results of the study showed that fun cooking activities indirectly collected algorithmic tasks in the problem-solving process through the activity process that was passed.